A new cosmological argument from grounding. (18th November 2019) - Deng, Duen-Min
Abstract: This paper presents a new cosmological argument based on considerations about grounding. I argue that, by assuming three plausible principles about grounding, we can construct a cosmological argument for the existence of a unique ungrounded being that ultimately grounds everything else. At the end of the paper I consider two possible objections, and offer my replies to them.